(untitled) (Jurnal Bahasa, 2007)
When discussing the function of clause as ideational representation - a way of representing patterns of experience, Halliday (1994) asserts that for that particular function, a clause normally consist of three ’nuln types of elements: process, participants, and circumstances According to him, circumstance element is realized by adverbial or prepositional group. The circumstance element or in some grammar books named as adverb is less described in formal syntax. Based on Halliday (1994) functional grammar and Asmah (1986), this paper discusses the circumstance element which is located at the beginning of the sentence, named ’marked Theme’ in the national laureate A. Samad Said discourse. The discussion covers its forms andlime-tions in representing the patterns of experience in discourse.